The shame that lingers: a survivor-centered critique of Catholic sin-talk - Starkey, A. Denise (American university studies / 7, 2009)
Introduction -- Narrating the suffering of child abuse and trauma -- Awakening from the nightmare : the origins of child maltreatment -- Child maltreatment in the Ancient and Middle Ages -- The ambiguity of the Christian contribution -- The current situation of violence against children -- The advent of awareness of child maltreatment -- Telling the truth of child maltreatment -- What constitutes child abuse? -- Secrecy, betrayal, isolation -- The traumatic aftermath of violence -- Posttraumatic stress disorder and childhood violence -- An implosion of the self : the study of shame -- The legacy of shame -- Shame in the ancient world -- Shame in Judaism and Christianity -- Shame in modernity -- Toward an understanding of shame -- The experience of shame -- The embodiment of shame -- Shame and emotion -- Distinguishing between shame and guilt -- Shame and empathy -- Coping with shame -- Cognitive and affective models -- Ways of avoiding shame -- Chronic shame and shame-based identity -- The compass of shame -- Shame as a consequence of trauma -- The sinned-against and the shame of sin-talk -- A perspectival shift to the sinned-against -- A review of sin-talk in the tradition -- Augustine's original sin -- Sin as acts : the legal approach -- Persistence of the juridical model -- Feminist deconstructions of sin -- Gendered sin-talk -- Sexism as original sin -- The glorification of suffering -- The problem of shame in sin-talk -- Shame in Augustine -- The hierarchy's deflection of shame -- Ashamed of scandal : zero tolerance as a case study -- Sin and identity -- Implications of a new angle of vision -- The other in confession : silence, shame, subjectivity -- Confession in the post-conciliar age -- The legacy of shame in confession -- Understanding contemporary resistance -- Women and confession -- The grammar of shame -- A rhetorical model of violence -- First rule in a grammar of shame : self-blame and culpability -- Second rule in a grammar of shame : internalizing religious and idealized images -- Third rule in a grammar of shame : surrendering to silence -- The oscillating rhythm of testimony and witnessing -- The necessity of testimony -- The impossibility of testimony -- Testimony as a genuine advent -- Witnessing as a condition for subjectivity -- The necessity of witnessing -- Obstacles to witnessing -- Toward an ethics of witnessing -- Movements toward flourishing -- Reviewing the argument four key threads -- First thread: A perspectival shift to the sinned against -- Second thread: Critiquing the juridical model of sin talk -- Third thread: The harmful grammar of shame -- Fourth thread: Testimony and an ethics of witnessing -- Some implications for flourishing -- The critical principle of flourishing -- Is shame consistent with a principle of flourishing? -- The possibility of shame-free discourses of sin -- Confession as a mutual dialectic of listening and speaking -- A final implication : God's silence or God's listening